Building Strategy and Performance - Warren, Kim (Open textbook library., 2012)
This book uses a balanced blend of frameworks and illustrations to teach you how to tackle the challenge of driving performance into the future. Kim Warren takes special care with this new textbook, Building Strategy and Performance, to ensure that it delivers instruction on how to deliver strategy powerfully over a sustained period of time. This book helps you to show your students where the levers are that they can control and how to choose what to do, when, and how much to achieve their specific goals. This book effectively outlines the dynamics of strategy, how one drives performance - past, today and into the future. It shows what causes performance to improve or deteriorate and what your students can do to change this trajectory for the better. But don't take our word for it, review the book now to see if it can help you to deliver the kind of tactical strategy course you desire for your students.